Williams hematology - Kaushansky, Kenneth; Williams, William J. (New York : McGraw-Hill Medical, 2010)
A comprehensive textbook outlining all facets of hematology--Provided by publisher.
Rev. ed. of: Williams hematology / editors, Marshall A. Lichtman ... [et al.]. 7th ed. c2006.
Includes bibliographical references and index.
Keywords: Hematologic Diseases